Neuropsychological Rehabilitation in Mild and Moderate Alzheimer’s Disease Patients - Renata Ávila; Isabel A. M. Carvalho; Cássio M.C. Bottino; Eliane C. Miotto (Behavioural Neurology, 2007)
Objective: The purpose of this study was to analyze the effect of a neuropsychological rehabilitation (NR) program on patients with Alzheimer’s disease (AD).